2015
DOI: 10.1248/cpb.c15-00607
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Biological Evaluation, and Antioxidant and Cytotoxic Activity of Heteroatom-Substituted 1,4-Naphtho- and Benzoquinones

Abstract: In the present paper, we report the synthesis, characterization, and biological evaluation as antifungal, antibacterial, antioxidant, and cytotoxic/anticancer agents of N-, S-, O-substituted-1,4-naphtho-and 2,5-bis(amino-substituted)-1,4-benzoquinone derivatives. In the synthesized compounds, antimicrobial activity at low concentrations against Escherichia coli B-906, Staphylococcus aureus 209-P, and Mycobacterium luteum B-917 bacteria and Candida tenuis VKM Y-70 and Aspergillus niger F-1119 fungi in compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Thus, exclusively 2-and/or 2,5-isomer were formed due to electrostatic reasons for compounds 17-25. The results agree well with the corresponding mechanism in the similar compounds [6,26].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, exclusively 2-and/or 2,5-isomer were formed due to electrostatic reasons for compounds 17-25. The results agree well with the corresponding mechanism in the similar compounds [6,26].…”
Section: Resultssupporting
confidence: 89%
“…Natural and synthetic quinonoid compounds are well-known substances which possess a variety of biological properties such as anticancer, antibacterial, or antimalarial drugs as well as fungicides [1]. The heterocyclic derivatives of 1,4naphthoquinones have been identified that have potent biological activities towards viral [2], molluscicidal [3], malarial [4], leishmanial [5], cancer [6], and bacterial and fungal diseases [7] due to their redox potentials [8]. Some of these pharmacological effects have been attributed to the formation of DNA-damaging anion-radical intermediates formed by bioreduction of the quinone nucleus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The naphthoquinone scaffold was an important pharmacophore found in a large number of biologically active compounds [7]. N-, S-, O-substituted-1,4-naphthoquinones are also reported to have good biological properties [8].…”
mentioning
confidence: 99%
“…Antibacterial and antifungal activity of S,Ncontaining derivatives of quinones has been studied in our laboratory previously [12,13] . Depending on the substituent, the results of antimicrobial activity of synthesized compounds differed in the degree of influence on bacteria and fungi.…”
mentioning
confidence: 99%